Surgical Quality Improvement - Kelz, Rachel R.; Wong, Sandra L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This unique handbook is designed for surgeons involved in personal, programmatic, institutional, regional or national QI efforts. The book highlights key quality improvement principles that relate to the care of the surgical patient. Theories as well as practical tips regarding quality improvement are gathered for this outstanding resource. Aimed at surgical residents and young surgical faculty, Success in Academic Surgery: Surgical Quality Improvement is written by expert authors who are members of the Association for Academic Surgery. No similar book directed at surgeons exists, and this is a timely and comprehensive QI resource for trainees, educators, and surgical leaders.
1. Quality Improvement in Surgery -- 2. The science of quality improvement -- 3. Measuring Surgical Quality -- 4. Are you capable of providing high quality care? -- 5. Surgical Quality Improvement: Local quality improvement -- 6. How to address a quality problem -- 7. Barriers and pitfalls in quality improvement -- 8. Conflict Resolution -- 9. Teaching quality improvement -- 10. Is 'quality science' human subjects research? -- 11. Academic careers in quality improvement -- 12. National Quality Improvement: Federal Regulation, Public Reporting, and the Surgeon -- 13. The public perception of quality improvement in surgery.
Keywords: Medicine; Health administration; Surgery; Practice of medicine; Medicine & Public Health; Practice and Hospital Management; Surgery; Health administration